2021
DOI: 10.3390/cancers13112769
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Ablation Compared to Partial Hepatectomy for Recurrent Colorectal Liver Metastases: An Amsterdam Colorectal Liver Met Registry (AmCORE) Based Study

Abstract: The aim of this study was to assess safety, efficacy and survival outcomes of repeat thermal ablation as compared to repeat partial hepatectomy in patients with recurrent colorectal liver metastases (CRLM). This Amsterdam Colorectal Liver Met Registry (AmCORE) based study of two cohorts, repeat thermal ablation versus repeat partial hepatectomy, analyzed 136 patients (100 thermal ablation, 36 partial hepatectomy) and 224 tumors (170 thermal ablation, 54 partial hepatectomy) with recurrent CRLM from May 2002 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…Local ablation has been shown to significantly increase survival time and enhance the quality of life for patients with liver metastatic tumors, with fewer complications and shorter hospital stays compared with surgical treatment. 10 For example, HIFU ablation of 47 patients with liver tumors <3 cm in diameter resulted in a tumor ablation rate of 87.2%. 11 And in a retrospective study, Zhang et al 12 compared the therapeutic efficacy of percutaneous RFA to MWA in liver tumor 5 cm in diameter by evaluating 155 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Local ablation has been shown to significantly increase survival time and enhance the quality of life for patients with liver metastatic tumors, with fewer complications and shorter hospital stays compared with surgical treatment. 10 For example, HIFU ablation of 47 patients with liver tumors <3 cm in diameter resulted in a tumor ablation rate of 87.2%. 11 And in a retrospective study, Zhang et al 12 compared the therapeutic efficacy of percutaneous RFA to MWA in liver tumor 5 cm in diameter by evaluating 155 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Prospective evidence by Dijkstra et al, in contrast, found no difference between LPFS, distant-PFS or OS between RFA and surgery in patients with mostly single metastases (64.5% of patients) and with small lesions < 3 cm (84% of patients). There were no difference in complications but significantly smaller hospital stay in patients treated with RFA [ 75 ].…”
Section: Local Ablative Therapiesmentioning
confidence: 99%
“…Recently, increasing attention has been focused on multimodal treatment strategies, meaning that the single or repeated applications of locoregional and systemic therapies are considered potentially more effective in providing long-term survival than chemotherapy alone [ 13 , 14 ]. Indeed, good results have been reported using ablative techniques or transarterial therapies, which, as an alternative to or in combination with systemic therapy for CRLMs patients [ 15 , 16 , 17 , 18 ], can also be applied to patients with CRLMs recurrence after a given previous locoregional treatment [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%